Purgatory - Edel, Uli.; Schneider, Dan.; Dawson, Gordon; Shepard, Sam, 1943-2017.; Roberts, Eric.; Stormare, Peter; Rowe, Brad, 1970-; Wahlberg, Donnie, 1969-; Souther, J. D.; Heinle, Amelia, 1973-; Fiedel, Brad.; Rosemont Productions; et al. ([United States] : TNT ; Burbank, CA : Distributed by Warner Home Video, 2005)
Wild Bill Hickock, Doc Holiday, Jesse James, Billy the Kid and more deceased greats of the untamed West get a last chance to undo their violent pasts in a mysterious town that's West of the Pecos and south of Eternity.
DVD, region 1, full screen presentation; Dolby Digital stereo.
English or Spanish dialogue; closed-captioned.
Sam Shepard, Eric Roberts, Peter Stormare, Brad Rowe, Donnie Wahlberg, John David Souther, Amelia Heinle.
Director of photography, William Wages ; editor, Mark Conte ; music, Brad Fiedel.
Originally broadcast as a made-for-TV movie in 1999.
MPAA rating: Not rated.
Keywords: Outlaws -- West (U.S.) -- Drama; Future life -- Drama; Proscritos -- Oeste (Estados Unidos) -- Teatro; Vida futura -- Teatro; Made-for-TV movies; Western television programs; Video recordings for the hearing impaired; DVD-Video discs; Western television programs